2013
DOI: 10.1111/cdev.12071
|View full text |Cite
|
Sign up to set email alerts
|

Do Time in Child Care and Peer Group Exposure Predict Poor Socioemotional Adjustment in Norway?

Abstract: Extensive exposure to nonparental child care during the first 4.5 years of life has been demonstrated in some American studies to negatively affect children's socioemotional functioning. Data from 935 preschool children who averaged 54.9 (SD = 3.0) months of age, from Trondheim, Norway were used to examine whether such negative effects, would emerge in Norway, a country with a different child-care system. The children's externalizing problems and social competence were unrelated to their child-care experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 63 publications
0
16
1
1
Order By: Relevance
“…At T1, Trondheim Early Secure Study children averaged 5538 hours in day care, 31 and their day care teachers thus had ample time to observe and evaluate them. These teachers should therefore be well positioned to evaluate the extent to which problems Step 1…”
Section: Burden and Problem Recognitionmentioning
confidence: 99%
“…At T1, Trondheim Early Secure Study children averaged 5538 hours in day care, 31 and their day care teachers thus had ample time to observe and evaluate them. These teachers should therefore be well positioned to evaluate the extent to which problems Step 1…”
Section: Burden and Problem Recognitionmentioning
confidence: 99%
“…A recent study in the UK also found that more time in centre-based care was associated with more behavioural difficulties 8. However, studies from Norway have shown little evidence that greater time in care is associated with children's externalising problems 9 10. There is inconclusive evidence regarding associations between the time spent in different types of childcare and children's cognitive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The mothers feeling of ambivalence towards the medication for the child are described in other studies [4]. Solheim and Wichstrøm [29] describes that 7.8% of the child population (aged 4 years) rate within the highest SDQ . This reflects the need for support and supervision that these parents need, both from their social network [8] and from professionals such as the public health nurse [25].…”
mentioning
confidence: 96%